The Correlation Between Vocabulary Acquisition and Reading Comprehension in Narrative Texts of Junior High School Students - A. Nur Ismi; Syarifah Farahdiba; Sultan Baa (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aimed to analyze students' vocabulary acquisition and reading comprehension in narrative texts and determine whether there was a correlation between vocabulary acquisition and reading comprehension in narrative texts while considering the frequency of vocabulary acquisition. The research employed a correlational study, involving bivariate and partial correlation analyses. The participants of this study were eighth-grade students at SMP Negeri 26 Makassar. The findings showed that most students' range scores were in the very poor category regarding vocabulary acquisition and reading comprehension in narrative texts. This study found a significant correlation between students' vocabulary acquisition and reading comprehension in narrative texts. The partial correlation analysis also showed a moderate correlation between the two variables with the frequency of vocabulary acquisition as a control variable. Thus, both variables were correlated with the frequency of vocabulary acquisition, indicating that the more frequently students acquired vocabulary, the better their vocabulary acquisition and reading comprehension in narrative texts.